Nurses’ perception of work and life under COVID-19 pandemic conditions: a qualitative study - Maghsoodi, Esmaiel; Vanaki, Zohreh; Mohammadi, Eesa (Frontiers in Public Health, 2023)
Objectives Although nurses work and live in special and stressful conditions due to the nature of their profession, in periods of crises and pandemics, when the work pressure on nurses and the public’s need for professional services increases to extraordinary and incomparable levels compared to customary conditions, their work and life situation becomes entirely different. Therefore, what nurses experienced in the COVID-19 pandemic went beyond the typical challenges of their work environment. This study was conducted to discover nurses’ perceptions of work and life during the COVID-19 pandemic. Methods This qualitative study was conducted with a conventional content analysis approach on 16 nurses working in the inpatient wards during the COVID-19 pandemic in Iran. Data were collected through unstructured, individual, and in-depth interviews between August 2020 and June 2023 and were analyzed using content analysis with the conventional (inductive) approach of Granheim and Lundman. Results Data analysis led to the extraction of 11 subcategories, namely, “feeling a lack of support and understanding from managers,” “team cooperation and communication challenges in difficult work conditions,” “shadow of burnout,” “shortage inequity,” “dissatisfaction with unfair wages and benefits,” “not having their work and sacrifices appreciated,” “suffering and fatigue of using personal protective equipment (PPE),” “deprivation of entertainment and rest,” “fear of illness and imminent death,” “low resilience,” and “deteriorating life conditions” These 11 subcategories led to the following themes: “unsafe work environment” and “the shadow of suffering and death.” Conclusion Nurses working in COVID-19 wards in Iran worked in an unsafe work environment during the COVID-19 pandemic and had to deal with suffering and fear of death. It is necessary to pay attention to the needs and problems of nurses, and healthcare organizations must provide the required support to maintain the physical and mental health of nurses during epidemics.